Accelerating business-to-business contract negotiations: Moving from one-sided to balanced standard contract terms. (December 2021) - Bretan, Hal; Lando, Henrik
Many businesses adopt one-sided boilerplate contract terms and conditions that lead to protracted negotiations. Often, the parties ultimately reach a compromise that could have been reached sooner if they had put forward more balanced contract terms at the outset. We ask why this seemingly irrational behavior persists and suggest a different approach. A dominant theory suggests that putting forward balanced terms may be seen as a sign of a weak bargaining position. We argue, however, that agency conflicts and cognitive biases often better explain such behavior. Moreover, we advocate a speed-to-contract strategy where the parties elect to use more balanced (value-maximizing) terms from the outset, and thereby avoid costly negotiations as well as delays in realizing the benefits of a transaction.